2015
DOI: 10.4103/1305-7456.156848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage solutions on microhardness of crown enamel and dentin

Abstract: Objective:The aim of this study was to determine alterations in microhardness of crown dentin and enamel, after 2 and 12-month storage in de-ionized water, 0.2% glutaraldehyde, Hanks’ Balanced Salt Solution (HBSS), 0.1% sodium hypochlorite (NaOCl) or 0.1% thymol.Materials and Methods:Freshly extracted, nonsterile 60 intact human premolars were distributed to five groups. Six teeth from each group were evaluated after two, and other six teeth were evaluated after 12 months storage. After grinding and polishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 20 publications
2
42
0
2
Order By: Relevance
“…These solutions might weaken the tooth substance. [ 42 43 ] For this study, the teeth were disinfected by chloramine-T and glutaraldehyde cacodylate solution, which was also accepted by other authors. [ 42 43 44 45 ] Other previous studies have shown that the disinfection of the teeth did not significantly affect the obtained results.…”
Section: Discussionmentioning
confidence: 99%
“…These solutions might weaken the tooth substance. [ 42 43 ] For this study, the teeth were disinfected by chloramine-T and glutaraldehyde cacodylate solution, which was also accepted by other authors. [ 42 43 44 45 ] Other previous studies have shown that the disinfection of the teeth did not significantly affect the obtained results.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, teeth kept up to 2 months in deionized water, glutaraldehyde, HBSS, NaOCl, or in thymol solutions can be used for mechanical in vitro tests. [22] Further studies are required to evaluate the efficacy of propolis, A. vera, and PJ as storage media at time interval from 30 min to 24 h.…”
Section: Discussionmentioning
confidence: 99%
“…The root tips were cut off to clean also the root channels and pulp chambers. Subsequently, the teeth were stored in 0•1% aqueous thymol solution 45 in order to avoid any unwanted effects from desiccation or bacterial decay of the organic phase. For the experiments, the authors used the incisors and canines due to their geometrical and morphological resemblance to human teeth.…”
Section: Bovine Tooth Enamel Modelmentioning
confidence: 99%